2008
DOI: 10.1186/1751-0759-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Does psychological status influence clinical outcomes in patients with inflammatory bowel disease (IBD) and other chronic gastroenterological diseases: An observational cohort prospective study

Abstract: BackgroundWhether there is a temporal relationship between psychological problems and clinical outcomes in patients with diseases of the digestive tract has not been widely researched. Thus, our aims were 1) To observe and compare prospectively clinical outcomes in relation to psychological co-morbidity in patients with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS) and chronic hepatitis C (HCV) and, 2) To test the hypothesis that patients with psychological co-morbidities are less likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
1
47
1
1
Order By: Relevance
“…We reviewed 20 eligible publications reported between 1990 and 2008 [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. 2 studies were published by Levenstein et al [20, 22], 2 by Bitton et al [10, 19], and 2 by Maunder et al [12, 13], each based on different data.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 20 eligible publications reported between 1990 and 2008 [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. 2 studies were published by Levenstein et al [20, 22], 2 by Bitton et al [10, 19], and 2 by Maunder et al [12, 13], each based on different data.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been questioned whether there is any relationship between psychological functioning and disease status 59 . However, studies that were more adequately powered to detect differences have found that distress levels change in parallel with disease activity 11,16,60 , and those in relapse have poorer quality of life than those in remission 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastroenterologists reported that antidepressants were successful in reducing pain, gut irritability, and urgency of defecation. In the most recent retrospective case-note audit of 287 patients, 83 (28.9%) patients had used an antidepressant at some time in their life [56][57][58][59] . Nonetheless, the design of the study does not allow a firm statement to be made about whether antidepressants improved the course of IBD.…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%